Implementação de rede de fibra óptica para as escolas públicas do município de Marapanim/Pará - PAIXÃO, Cristiano Barroso da (2023)
This course conclusion work aims to bring quality internet signal to all public schools in the municipality of Marapanim to generate digital inclusion. teaching and all the necessary configurations for the implementation. The practical work presented satisfactory results, which enabled the elaboration of this project.